2015
DOI: 10.1016/j.applthermaleng.2015.06.033
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the potential recovery of compressor heat losses to enhance the efficiency of refrigeration systems by means of thermoelectric generation

Abstract: ElsevierNavarro Peris, E.; Corberán Salvador, JM.; Ancik, Z. (2015). Evaluation of the potential recovery of compressor heat losses to enhance the efficiency of refrigeration systems by means of thermoelectric generation. Applied Thermal Engineering. AbstractThe present study evaluates the possibilities of increasing the efficiency in refrigeration and heat pump systems based on compression cycles by means of using the compressor heat losses. In order to do that, the work been divided in the following parts: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 11 publications
0
9
0
1
Order By: Relevance
“…According to the heat transfer principle, the energy conversion principle of thermoelectric module can be expressed by eqs. (9)- (11), which h Q is the heat absorbed by the hot end of thermoelectric module from the heat source, C Q -the heat flowing into the cold end of thermoelectric module to the cold source, tm Q -the heat transmitted through the thermocouple pair and air gap:…”
Section: Model Buildingmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the heat transfer principle, the energy conversion principle of thermoelectric module can be expressed by eqs. (9)- (11), which h Q is the heat absorbed by the hot end of thermoelectric module from the heat source, C Q -the heat flowing into the cold end of thermoelectric module to the cold source, tm Q -the heat transmitted through the thermocouple pair and air gap:…”
Section: Model Buildingmentioning
confidence: 99%
“…Shi et al [10] finds that changing the geometry or number of thermocouples can only increase the output voltage or current, but cannot increase the output voltage or current at the same time. Experiment shows that the change of temperature and heat transfer conditions at the cold end has little effect on the output performance [11]. At the same time, researchers found that contact pressure, cold source structure and cooling mode also affect the output performance of thermoelectric generator [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Актуальность поставленной цели обусловлена тем, что вся энергия, генерируемая в ДВС и затрачиваемая на сжатие газа в мобильной компрессорной установке, выбрасывается в окружающую среду в виде тепла. Рекуперация этой тепловой энергии обратно в установку в механической форме представляет собой актуальную научно-техническую задачу [5][6][7][8][9][10][11][12][13][14]. Известно, что рекуперация данных тепловых потерь может позволить вдвое увеличить производительность установки и уменьшить расход топлива на её привод.…”
Section: постановка задачиunclassified
“…Thermoelectric materials, modeling approaches and applications were reviewed in another study and Thermoelectric cooling applications (electronic cooling systems, domestic refrigeration, and air conditioning of automobile) were analyzed [2]. Vapor compression heat pump systems and also refrigerator systems were investigated in detail to enhance their efficiency employing thermoelectric generation by using compressor heat losses [3]. Performance of vapor compression heat pump were analyzed using different types of lubricating oil for a system operated by a reciprocating compressor [4].…”
Section: Introductionmentioning
confidence: 99%